Evaluation of accuracy of one-step nucleic acid amplification (OSNA) in diagnosis of lymph node metastases of papillary thyroid carcinoma. Diagnostic study. (October 2019) - Medas, Fabio; Coni, Pierpaolo; Podda, Francesco; Salaris, Claudia; Cappellacci, Federico; Faa, Gavino; Calò, Pietro Giorgio
Abstract: Background: The incidence of node metastases in papillary thyroid carcinoma (PTC) is high, ranging from 20% to 90%. Prophylactic central lymph node compartment dissection (CLND), suggested from the latest guidelines for high-risk tumors, meets resistance due to the high incidence of postoperative complications. Recently, new molecular biologic techniques, such as One Step Nucleic Acid Amplification (OSNA), have spread widely, allowing to quickly isolate, amplify and quantify mRNA encoding for proteins selectively present in neoplastic cells, as Cytokeratine-19. The aim of this study is to evaluate the application of OSNA to intraoperative diagnosis of node metastases of PTC. Methods: We included in the study patients with preoperative diagnosis of PTC; from each patient one or more lymph nodes were collected. To assess OSNA accuracy, each lymph node was divided into two halves: the first one was analysed with histopathological and immunohistochemical examination, whereas the second was studied with OSNA. Results: Twenty-six lymph nodes from 13 patients were included in the study. Overall, OSNA sensitivity was 87.5%, specificity 94.4%, positive predictive value 87.5%, negative predictive value 94.4% and accuracy 92.8%. Discussion and conclusion: OSNA is effective in detecting lymph node metastases of PTC. Considering the high risk of complications in CLND, and the uncertain prognostic value of lymph node metastases of PTC, OSNA seems to be a promising tool to identify intraoperatively patients who may benefit from CLND. Highlights: Prophylactic central lymph node dissection in patients with differntiated thyroid carcinoma is not universally adopted due to high incidence of postoperative complications. One Step Nucleic Acid Amplification (OSNA) allows to quickly isolate, amplify and quantify mRNA encoding for proteins selectively present in neoplastic cells. OSNA is effective in diagnosis of lymph node metastases of differentiated thyroid carcinoma.